2018
DOI: 10.1245/s10434-018-6455-0
|View full text |Cite
|
Sign up to set email alerts
|

Value of Preoperative PET-CT in the Prediction of Pathological Stage of Gastric Cancer

Abstract: PET-CT appears to be a useful complementary modality in the assessment of pStage III/IV because of the high sensitivity of FDG uptake in the primary tumor and the high specificity of FDG uptake in the lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
0
22
1
Order By: Relevance
“…subcentimetre. Our reported specificity in lymph nodal status is much higher than the sensitivity, 73%, although this figure is lower than that reported by others [33,29]; this was possibly due to patients in our surgical cohort who underwent neoadjuvant chemotherapy and downstaging. Interestingly, recent studies specifically examining the significance of nodal FDG avidity have found poorer prognosis among patients with nodal FDG positivity, suggesting that PET-CT may identify a subset of cancers with a greater propensity to metastasise [11,29].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…subcentimetre. Our reported specificity in lymph nodal status is much higher than the sensitivity, 73%, although this figure is lower than that reported by others [33,29]; this was possibly due to patients in our surgical cohort who underwent neoadjuvant chemotherapy and downstaging. Interestingly, recent studies specifically examining the significance of nodal FDG avidity have found poorer prognosis among patients with nodal FDG positivity, suggesting that PET-CT may identify a subset of cancers with a greater propensity to metastasise [11,29].…”
Section: Discussioncontrasting
confidence: 81%
“…For the assessment of locoregional lymph nodal staging in gastric cancer, FDG PET-CT is more specific but less sensitive than CT alone [25][26][27]. However, recent studies have shown poorer prognosis for patients with FDG-avid nodes [11,28,29], suggesting an additional role for PET-CT in identifying patients at higher risk of metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Since the sensitivity and specificity of CT scan to identify metastatic lymph nodes remains unsatisfactory in gastric cancer patients, 18 FDG PET-CT scan is frequently used as a complementary tool to verify distant metastasis in gastric cancer patients with equivocal CT findings. PET-CT has demonstrated high specificity rate, ranging from 90.5 to 100% in detecting metastatic nodes of gastric cancer patients in recent studies, albeit with a markedly lower sensitivity of 22.7–58.3% [ [5] , [6] , [7] , [8] ]. Although infrequently encountered, false-positivity of PET-CT scans has been reported, including cases of metabolically active but benign diseases such as infection (including tuberculosis and aspergillosis), sarcoidosis, and other granulomatous diseases [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) historically has demonstrated lower sensitivity (22.7–58.3 %) but significantly higher specificity (90.5–100%) in detecting lymph node metastasis of gastric cancer compared to the commonly used CT scans, particularly in intestinal-type tumors [ [5] , [6] , [7] , [8] ]. FDG-PET integrated with CT can demonstrate anatomic and functional characteristics of the lesions at the same time in one image providing improved diagnostic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, preoperative detection of LNM has depended on imaging studies, such as contrast-enhanced computed tomography (CECT), upper endoscopy, and magnetic resonance imaging (MRI). Nevertheless, it is very challenging for these conventional modalities to accurately detect LNM because of their low sensitivities and specificities [10,11]. Therefore, additional methods are necessary to detect LNM before operation when imaging studies are unavailable or the results are not accurate.…”
Section: Introductionmentioning
confidence: 99%